The potential influence of LED lighting on mental illness. (2nd January 2018) - Bauer, Michael; Glenn, Tasha; Monteith, Scott; Gottlieb, John F.; Ritter, Philipp S.; Geddes, John; Whybrow, Peter C.
Abstract: Objectives: Two recent scientific breakthroughs may alter the treatment of mental illness, as discussed in this narrative review. The first was the invention of white light-emitting diodes (LEDs), which enabled an ongoing, rapid transition to energy-efficient LEDs for lighting, and the use of LEDs to backlight digital devices. The second was the discovery of melanopsin-expressing photosensitive retinal ganglion cells, which detect environmental irradiance and mediate non-image forming (NIF) functions including circadian entrainment, melatonin secretion, alertness, sleep regulation and the pupillary light reflex. These two breakthroughs are interrelated because unlike conventional lighting, white LEDs have a dominant spectral wavelength in the blue light range, near the peak sensitivity for the melanopsin system. Methods: Pertinent articles were identified. Results: Blue light exposure may suppress melatonin, increase alertness, and interfere with sleep in young, healthy volunteers and in animals. Areas of concern in mental illness include the influence of blue light on sleep, other circadian-mediated symptoms, prescribed treatments that target the circadian system, measurement using digital apps and devices, and adolescent sensitivity to blue light. Conclusions: While knowledge in both fields is expanding rapidly, future developments must address the potential impact of blue light on NIF functions for healthy individuals and those with mental illness.